2012
DOI: 10.1126/scisignal.2001878
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Inhibitors of Apoptosis Are Global Regulators of NF-κB and MAPK Activation by Members of the TNF Family of Receptors

Abstract: Tumor necrosis factor (TNF) family members are essential for the development and proper functioning of the immune system. TNF receptor (TNFR) signaling is mediated through the assembly of protein signaling complexes that activate the nuclear factor κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathways in a ubiquitin-dependent manner. The cellular inhibitor of apoptosis (c-IAP) proteins c-IAP1 and c-IAP2 are E3 ubiquitin ligases that are recruited to TNFR signaling complexes through their constitutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(183 citation statements)
references
References 60 publications
6
174
2
1
Order By: Relevance
“…Here, we show these effects in tumor cell lines and that a TWEAK blockade with an anti-TWEAK mAb, RG7212, results in significant tumor growth inhibition (TGI) in multiple tumor models expressing Fn14. These in vitro and in vivo data are consistent with tumor-promoting effects shown with other TNF family receptors lacking death domains (19,20) and with TWEAK data in disease models in animals and pathologic conditions in humans (21,22).…”
Section: Introductionsupporting
confidence: 86%
“…Here, we show these effects in tumor cell lines and that a TWEAK blockade with an anti-TWEAK mAb, RG7212, results in significant tumor growth inhibition (TGI) in multiple tumor models expressing Fn14. These in vitro and in vivo data are consistent with tumor-promoting effects shown with other TNF family receptors lacking death domains (19,20) and with TWEAK data in disease models in animals and pathologic conditions in humans (21,22).…”
Section: Introductionsupporting
confidence: 86%
“…Previous studies in HEK293 cells have shown that USP19 can deubiquitinate and stabilize cIAP proteins (Mei et al, 2011). These proteins can promote TNFα signaling in several cell types (Varfolomeev et al, 2012) and can also inhibit myogenesis in primary muscle cells (Enwere et al, 2012). So an attractive hypothesis is that USP19 might promote muscle atrophy by stabilizing cIAPs and activating the NFκB pathway.…”
Section: Usp19 and Skeletal Musclementioning
confidence: 99%
“…11,[26][27][28] Apart from these chemicals, a set of biological ligand of the TNF family, such as lymphotoxin LTα 1 β 2 , CD40L or Tweak, also appeared to target c-IAP1/2 toward the proteasomal and/ or lysosomal degradative pathways. [29][30][31][32][33][34] c-IAP1/2 depletion leads to NIK (NF-κB-inducing kinase) stabilization and the phosphorylation of both IKKα and NF-κB2/p100 prior to the processing of p100 into p52, a pathway defined as the alternative, or non-canonical, NF-κB pathway. [35][36][37] Genetic mouse models revealed that NIK is required for the proper development and/or maintenance of secondary lymphoid organs, for osteoclastogenesis, for T-cell activation as well for B-cell survival.…”
mentioning
confidence: 99%